European Parliament: between Elections and Action - ALEXANDRESCU, Mihai (Presa Universitară Clujeană, 2024)
This volume was conceived to discuss the role that the European Parliament (EP) has assumed within the European Union. The year 2024 marks the beginning of the EP’s tenth legislature since it was first directly elected by the citizens of the EU member states. The book brings together several contributions aimed at providing an in-depth approach to the functioning mechanisms of the EP and how it fulfils its mandate to represent European citizens. The purpose of this work is to analyse and better under-stand the role of the EP in the current decision-making context, especially during a time when the democratic legitimacy of Euro-pean institutions is intensely debated. The Parliament’’’’s evolution from a consultative to a legislative body displays the constant efforts to democratise the European decision-making process.